Adolescent Identity Development as a Factor of Aggression Construction - Khomyk, V. (Psychological Prospects Journal, 2013)
The thesis of the article is concerned with the hypothesis that youthful aggression depends upon the stage of identity development or epistemological failure, which exerts the internal pressure on the way of meaning-making and behavior. Thinking of young men reflects «seize-ness» in a maladaptive construction of self, when relationship between the individual and the holding environment is broken. This distortion is manifested in combinations of the constructions of that in which boys are different from others on the constructions of what they are like them in their inner world in which social melodramas can be played out.